Psychological Implications of Unemployment Among Bangladesh Civil Service Job Seekers: A Pilot Study - Rafi, Md. Abdur; Mamun, Mohammed A.; Hsan, Kamrul; Hossain, Moazzem; Gozal, David (Frontiers in Psychiatry, 2019)
Background: Recent trends suggest that university graduates seeking jobs are more susceptible to common mental disorders, such as depression, anxiety, or stress. However, the mental health issues among unemployed graduates has not been explored in Bangladesh yet. Aims: This study aimed to assess for the first time the prevalence and associated risk factors of depression, anxiety, and stress among Bangladesh Civil Service (BCS) job seekers. Three hundred four graduates residing in Rajshahi, Bangladesh, who were preparing to attend the 40th BCS examination, the most sought-after employment opportunity in the country, were surveyed. Methods: Measures included socio-demographics, field of study, and career-related variables, and the Bangla Depression Anxiety Stress Scale (DASS-21). Chi-square test, Fisher exact test, and binary logistic regression with “depression,” “anxiety,” and “stress” as the dependent variables were carried out to identify the factors associated with these. Results: Overall, the prevalence of moderate to extremely severe depression, anxiety, and stress was 49.3%, 53.6%, and 28.3%, respectively, with no detectable differences between genders. Insecurity related to a BCS job (OR = 0.41; CI = 0.26–0.65, p < 0.001; ref: job insecurity), family and social pressure to obtain a BCS job (OR = 4.58; CI = 1.67–12.56, p < 0.001), and stress (OR = 8.33; CI = 4.47–15.51, p < 0.001) emerged as independent predictors for depression. In addition, having part-time job was associated with anxiety (OR = 2.38; CI = 1.34–4.23, p = 0.003), and security in a BCS job and serving the nation through this job were negatively associated with stress (OR = 0.59; CI = 0.35–0.98, p = 0.042 vs. OR = 0.59; CI = 0.36–1.00, p = 0.05). Conclusion: The relatively high rates of depression, anxiety, and stress among graduate job seekers should prompt implementation of market force initiatives that incorporate interventions related to the major risk factors uncovered herein.